Clinical scenarios of suboptimal response to rituximab in relapsing ANCA-associated vasculitis - Sergio Prieto-González; Ellen Romich; Peter A. Merkel; David R. W. Jayne; Rona M. Smith; Giles Walters; Chen Au Peh; Dwarakanathan Ranganathan; Simon Carette; Nader Khalidi; Vladamir Tesar; Michael Clarkson; et al. (Frontiers in Medicine, 2026)
Background Rituximab is effective for induction and maintenance of remission in relapsing ANCA-associated vasculitis (AAV), but some patients do not achieve complete remission or experience relapse despite treatment. We aimed to describe the frequency, characteristics, and outcomes of patients with suboptimal response to rituximab within the RITAZAREM trial. Methods Post hoc descriptive analysis, including patients with granulomatosis with polyangiitis (GPA) or microscopic polyangiitis (MPA) treated with rituximab for induction ( N = 188) and those receiving rituximab maintenance ( N = 85). Three scenarios of suboptimal response were examined: (i) failure to achieve protocol-defined remission at month 4 ( n = 6); (ii) incomplete remission at month 4, defined as BVAS/WG = 1 ( n = 10); and (iii) relapse during rituximab maintenance ( n = 13). Data were summarized descriptively. Time to relapse from month 4 in patients with BVAS/WG = 1 versus BVAS/WG = 0 was explored using Kaplan–Meier analysis. Results Six of 188 patients (3%) did not achieve protocol-defined remission by month 4, 10 (5%) had residual low-grade disease activity (BVAS/WG = 1), and 13 of 85 patients (15%) receiving rituximab maintenance relapsed within 24 months during maintenance treatment. All patients with BVAS/WG = 1 at month 4 had a history of PR3-ANCA positivity and ear/nose/throat (ENT) baseline manifestations. Relapse occurred more frequently in this subgroup than in patients with BVAS/WG = 0, and time-to-relapse analysis showed shorter relapse-free survival, although interpretation is limited by the small sample size. Most first relapses were minor, and some patients subsequently experienced additional relapses, including major relapses. Conclusion In this exploratory and hypothesis-generating analysis, a small subset of patients with relapsing AAV showed suboptimal outcomes with rituximab. Residual disease activity at month 4, particularly in patients with PR3-ANCA positivity and ENT involvement, may represent a clinical subgroup associated with an increased frequency of earlier relapse, although this observation requires confirmation.